Trapped in a complex: the 1,2,4,5-Tetrakis(tetramethylguanidino)benzene radical cation (ttmgb+·) with a Bisallylic Structure - Trumm, Christine Helga; Hübner, Olaf; Kaifer, Elisabeth; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2010)
In this work we follow the reaction of the strong electron donor 1,2,4,5-tetrakis(tetramethylguanidino)benzene (ttmgb) with CuII nitrate. Three binuclear CuII complexes were isolated as products of this reaction. Depending on the reaction conditions, especially the molar ratio of the two reactants, the ttmgb ligand in these complexes is neutral, mono- or dicationic. All three complexes were structurally characterized. In addition to the experimental studies, quantum chemical calculations were carried out, which, in combination with experimental magnetic (SQUID) curves, especially shed light on the magnetic superexchange. The binuclear CuII complex of the ttmgb radical cation represents a three-spin system. The SQUID magnetic data as well as the results of quantum chemical calculations indicate strong ferromagnetic copper-ligand coupling.